Antimicrobial and Anti-Inflammatory Activities of Extract from Macleya cordata (Willd) R. Br. in the Treatment of "Dry Socket" - K. Chytilová; A. Galandáková; J. Zapletalová; J. Pazdera (Czech Dental Chamber, 2013)
Introduction: "Dry socket" is the most common complication of wound healing after extraction of lower third molar that occurs in about 20% cases. For the local treatment of dry socket the antiseptic and antimicrobial medicaments completed with analgetics are used. Similar therapeutic effect of locally applied of Macleaya cordata extract (MCE; mainly due to the sanguinarine and chelerythrine content) could be presumed because the extract is used in the treatment of gingivitis and reduction of tooth plaque. Aim of work: The aim of clinical study was to examine anti-inflammatory effects of MCE in the treatment of dry socket which occurred after surgical removing of the lower third molar. Material and Methods: The clinical cohort included 60 patients with dry socket. Patients were divided into two groups. Group I (n = 25) was treated with MCE (0.03%, v/v). A resorbable collagen dental peg saturated with MCE was applied into extraction wound. Group II (n = 35) was treated with a classical method rinsing by means of antiseptic solution and application of antiseptic solution on gauze drain [Chlumsky (phenol campher)solution]. During the healing period, mucosal temperature with non-contact infra thermometer was evaluated as an objective marker. The intensity of pain monitored using a visual analogue scale was recorded as a subjective marker. The total therapy period and a prospective use of analgesics were booked in a questionnaire. Results: Significant differences in clinical course of diseases between groups of patients were found. Mucosal temperature and pain intensity have dropped quicker and duration of therapy has been reduced in patients topically treated with MCE when compared with conventionally treated controls. Conclusions: Clinical study has confirmed the remarkable anti-inflammatory effects of MCE previously demonstrated in vitro. A practical problem that remains to be resolve is the form and method of MCE application. The collagen dental peg as a vehicle did not work properly because of its porosity which in the wet environment of the oral cavity often caused its displacement outside of the extraction wound. A better alternative would probably be the application of active substances in the form of a thick gel.